975 RELATIONSHIP BETWEEN HAND GRIP STRENGTH (HGS) AND 10 YEAR PROBABILITY OF MAJOR OSTEOPOROTIC FRACTURES IN OLDER. (14th June 2022) - Obiechina, N; Nandi, A; Mubin, M; Khan, R; Chan, R; Pathmanathan, K; Titheridge, L; Tse, N; Kachala, P; Rahman, S; Mukherjee, B
Abstract: Introduction: HGS has been shown to be associated with adverse outcomes in a wide range of conditions. It has also been found to be associated with bone mineral density and is inversely associated with risk of osteoporotic fractures. The aim of this study was to determine the association between HGS and 10 year probability of sustaining a major osteoporotic fractures in older inpatient and to evaluate the effect of gender on this association. Method: This was a cross-sectional, observational analysis of older patients admitted into hospital between September and November 2021. HGS was measured in these patients using the JAMAR hydraulic hand held dynamometer. The Southampton protocol was used. The FRAX UK tool (without BMD) was used to calculate 10 year probability of major osteoporotic fractures. Patients were included if they were 60 years and above. Younger patients were excluded as were stroke patients. Patients with incomplete data were excluded from analysis. The SPSS 27 package was used for statistical analysis. Baseline characteristics were calculated using descriptive statistics. Pearson's correlation coefficient and linear regression were used to calculate correlation. Results: 104 patients were analysed—41 males and 63 females. Mean age was 83 years (SD 8.2). Grip strength was inversely correlated with FRAX UK in predicting 10 year probability of major osteoporotic fractures in all patients, male patients and female patients (r = −0.452; p < 0.001, r = −0.351; p = 0.02 and r = −0.271; p = 0.03 respectively). Conclusion: Grip strength is negatively associated with increased probability of major osteoporotic fractures in older inpatients. Reference(s) Ma Y, Fu L, Jia L, et al. Muscle strength rather than muscle mass is associated with osteoporosis in older Chinese adults. J Formos Med Assoc. 2018;117(2):101–108. doi:10.1016/j.jfma.2017.03.004